THE ARAB'S «PEACE PLAN» ON SYRIA ON THE PAGES OF «AL-SHARQ AL-AWSAT» - A. Baranov (Гуманитарные и юридические исследования)
The events of the Arab Spring 2011 in the Middle East caused a change in the balance of power in the regional security system. Saudi Arabia, claiming to be a regional power, naturally tried to take advantage of the current situation during the aggravated confrontation in Syria between the government of Bashar al-Assad and the opposition. Refraining from open interference in the internal affairs of Syria, Saudi Arabia is actively resorting to "information confrontation" in the media. One such instrument of influence on world public opinion is the «Al-Sharq Al-Awsat» newspaper, which reflects the official policy of the Kingdom of Saudi Arabia. The article, based on the materials of the «Al-Sharq Al-Awsat» newspaper, which is projecting the official Saudi Arabian politics to the world community, analyzes the perception and reaction to the «peace plan» proposed by the League of Arab States at the end of 2011 to resolve the conflict in Syria. It analyzes the selection and presentation of material in the description of the events of the newspaper related to the discussion and adoption of this plan, the activities of the mission of the LAS observers in Syria, and the reaction to this activity of the representatives of the Syrian opposition, whose information mouthpiece was «Al-Sharq Al-Awsat». Based on the analysis, it is concluded that the editorial policy of the newspaper was aimed at creating a negative image of President Bashar al-Assad among the Arab and world public opinion as a «bloody» dictator with whom it is unacceptable to negotiate, the position of a «tough» approach and decisive actions aimed at overthrowing the Syrian regime. In fact, Saudi Arabia, through this media tool, actively influenced public opinion, preparing it for the active phase of its participation in resolving the Syrian crisis after 2011.